Streamlined mail-based methods for large randomised trials: lessons learnt from the ASCEND study - Mafham, Marion M. (Diabetologia, 2019)
Reliable assessment of the effects of an intervention usually requires large randomised trials but such studies are becoming increasingly complex and costly to run. ‘Streamlined’ trials are needed in which every aspect of the trial design and conduct is simplified, retaining only those elements needed to answer the research question and ensure the safety of the individual participants. In this review we discuss how the trial ‘A Study of Cardiovascular Events iN Diabetes’ (ASCEND) was streamlined. The study included a two-by-two factorial design: it assessed the effects of low-dose aspirin and, separately, supplementation with n-3 fatty acids on serious vascular events in 15,480 people with diabetes but no overt cardiovascular disease. Other key streamlined design features, such as mail-based recruitment and follow-up, mainly by post, with no in-person visits and use of a run-in period, are also described. We go on to discuss the success of the study and other studies that have employed a similar mail-based approach, and the type of clinical trials that are suitable for mail-based design. Finally, we consider the limitations of the study, and how these could be circumvented in future studies. ASCEND randomised large numbers of eligible participants, achieved good adherence rates and almost complete follow-up at a fraction of the cost of traditional clinic-based trials. Such studies are necessary if researchers are to address the important clinical questions most relevant to improving health.